The sixty-year anniversary of high Medical College of Professional Health Studies in Belgrade and sixty-five years of higher education of nurses - Kekuš Divna (Sestrinska reč, 2018)
High Medical College of Professional Health Studies in Belgrade (Higher Medical School in Belgrade) was established on January 17, 1958, as the first higher medical school in the National Republic of Serbia. Education of higher education staff for work in health-social institutions, as well as for work in the hygiene service and sanitary inspection, was the basic task the school started work with. The school had departments for a senior nurse and a senior sanitary technician. The school is celebrating sixty years since it was founded and sixty-five years from the beginning of nursing education at a higher level, since the first high school for the nurses of the Yugoslav Red Cross was established in 1952. At this moment the School has its own space, applies the Bologna Declaration in the education of nurses and other health profiles and has more than twenty accredited study program of basic and specialist studies. The personnel structure corresponds to European standards, so today the school has more than 30 Doctors of Science (PhD) and 35 Masters (MSc) and medical specialist from the field of medical sciences predominantly.